FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA TAHUN 2011 – 2013 - Theresia Dian Widyastuti (Universitas Ahmad Dahlan, 2016)
This study was conducted to analyze the effect of liquidity, leverage, profi tability, cash fl ow ratio, company size, growth, quality audits, and audit lag on the issue of going concern audit opinion of manufacturing companies listed in Indonesia Stock Exchange in year 2011 - 2013. The study was conducted on 72 samples of manufacturing companies selected. Binary logistic regression testing is used as statistical test. The results of this study showed that leverage and audit quality had signifi cant impact on the issue of going concern audit opinion, whereas liquidity, profi tability, cash flow ratio, company size, growth, and audit lag had no signifi cant impact on the issue of going concern audit opinion.